China and America: Destined for Conflict? - Tao, Wenzhao. author. aut Link
XXI, 286 p. 2 illus., 1 illus. in color.
Keywords: This book explores the possibility and feasibility of building a new model of major-country relations between China and the United States, which is of great significance to the sound interaction between the two countries and the preservation of peace and stability of the world. In early June 2013, Chinese President Xi Jinping and US President Barack Obama reached a consensus on building a new model of major-country relations at the historical Sunny lands meeting in California. In the years that followed, the two leaders were committed to that goal despite the different interpretations in its substance. How is the new model of major-country relations conceptualized and developed? What renders it possible? Is the major-country conflict inevitable? These are the basic issues addressed in this book. Now, China-US relations are at a critical juncture. The international community is watching the world’s two largest economies and is quite concerned about the future of one of the world’s mostcomplicated bilateral relationships. This timely publication of Professor Tao Wenzhao provides us with a realistic approach to managing this vital relationship in a candid and balanced way.